Are We Overusing Coagulation Studies in the Emergency Department? - Bader Alyahya; Abdulaziz Alalshaikh; Ali Alkhulaif; Tareq Al-Salamah; Badr Aldawood; Alwaleed Alsubaie; Meshal Alohali; Saud Alshenaifi; Abdulaziz Alohali; Majed B. Alzin; Abdullah Almana; Mohammed Habib; et al. (Emergency Medicine International)
Background and Objectives. Blood tests are often indiscriminately requested in the Emergency department (ED) and many EDs have preset orders that are usually performed at triage before clinical assessment to improve the flow of patients through the department. We conducted this study to evaluate the frequency of requests for coagulation profile, the incidence of abnormal coagulation profiles and the unnecessary use of coagulation profile testing in our institution. Methods. This retrospective observational study, conducted in the ED of King Saud University Medical City (KSUMC) in Riyadh, Saudi Arabia, during July and August of 2021(2 months) examined coagulation profile requests. Patients’ demographic data (age and gender), medical and clinical history (presenting complaint, comorbidities, and diagnosis), the use of antiplatelets or anticoagulant agents and laboratory values for PT, APTT, and INR were collected. We calculated the total cost of unnecessary coagulation profile testing based on the independent assessment of two ED consultants. Results. Of 1,754 patients included in the study, 811 (46.2%) were males and 943 (53.8%) were females, with a mean age of 42.1 ± 18.5 years. There were 29 (1.7%) patients with liver disease and 21 (1.2%) patients had thromboembolic disease. The majority of the patients’ results were within normal levels of PT (n = 1,409, 80.3%), APTT (n = 1,262, 71.9%), and INR (n = 1,711, 97.4%). Evidence of active bleeding was detected in 29 patients (1.7%). Among patients with bleeding only one had an abnormal INR (3.01) and was on warfarin. Forty-six (2.6%) patients had elevated INR level. Cohen’s kappa between the two consultants was recorded at 0.681 (substantial agreement) in their assessment of the appropriateness of coagulation tests requests and both consultants believed that 1,051 tests (59.9%) were not indicated and were unnecessary. The expected annual cost saving if the unnecessary tests were removed would be around SAR 1,897,200 (approximately US$ 503,232) which is about SAR 180000 (US$ 48000)/1000 patients. Conclusion. This study showed that coagulation tests are overused in the ED. More than half of coagulation profile tests in our study population were deemed unnecessary and associated with significant cost. Targeted testing based on specific patient presentation and medical history can guide physicians in wisely choosing who needs coagulation studies.